Branded content the fateful merging of media and marketing - Hardy, Jonathan 1963- (Routledge, 2022)
"This is a critical study of the changing relationship between media and marketing communications in the digital age. It examines the growth of content funded by brands, including brands' own media, native advertising and the integration of branded content across film, television, journalism and publishing, online, mobile and social media. This ambitious historical, empirical and theoretical study examines industry practices, policies and 'problems', advancing a framework for analysis of communications governance. Featuring examples from the UK, US, EU, Asia and other regions, it illustrates and explains industry practices, forms and formats and their relationship with changing market conditions, policies and regulation. The book provides a wide-ranging and incisive guide to contemporary advertising and media practices, to different arguments and perspectives on these practices arising in industry, policy and academic contexts, and to the contribution made by critical scholarship, past and present. It also offers a critical review of industry, regulatory, societal and academic literatures. Jonathan Hardy examines the erosion of the principle of separating advertising and media and calls for a new framework for distinguishing marketing communications across 21st century communications. With a focus on key issues in industry, policy and academic contexts this is essential reading for students of media industries, advertising, marketing and digital media."--Provided by publisher.